A new species of the processid shrimp genus Nikoides Paul’son, 1875 (Decapoda: Caridea) from Japan - Komai, Tomoyuki; Hirabayashi, Isao (Zootaxa, 2021)
A new species of the processid shrimp genus Nikoides Paul’son, 1875, N. subdistalis, is described and illustrated on the basis of five specimens collected from Kushimoto, Wakayama Prefecture, Japan, at depths of 7–12 m. The new species appears most similar to N. maldivensis Borradaile, 1915 among the 10 known congeners, but is notable in the unique dentition of the rostrum and the characteristic shape of the antennular stylocerite. A partial segment of the mitochondrial 16S rRNA gene was sequenced from one of the paratypes of the new species, and genetic divergence among four congeneric taxa, of which three was downloaded from the GenBank database, is shown. An identification key to 11 species of Nikoides, including the new species, is given.